Effects of flow and heat transfer around a hand-shaped former - Kittipos Loksupapaiboon; Chakrit Suvanjumrat (Engineering Applications of Computational Fluid Mechanics, 2022)
Rubber glove manufacturing requires improvements in the curing process. In this study, the forced convection of hot airflow past a hand-shaped former, which has a typical shape in the rubber glove manufacturing process, was examined. A former model consisting of five fingers, palm, dorsum, and wrist was separated to investigate the convective heat transfer of the individual parts by OpenFOAM. The study conditions for the manufacturing process were a Reynolds number ranging from 15,837 to 63,351 and an angle of attack from 0° to 180°. After validating the computational fluid dynamics models with experiments and previous research, the k–ω shear stress transport turbulence model was appropriate. The angle of attack slightly affected the average Nusselt number on all parts of the hand-shaped former except the dorsum. An optimization method was employed to determine the optimal attack angle that caused the maximum convective heat transfer. The result was 0°. Therefore, the simulation results for the dorsal part at 0° established an average Nusselt number equation. This equation had an accuracy with an average error of less than 0.24% and an R2 of 0.9997. The average Nusselt number equation of the dorsal part is representative for analyzing the heat transfer in the curing process in rubber glove manufacturing.